PENERAPAN TEKNOPRENEURSHIP PADA PROSES PENGAWETAN BAMBU UNTUK SEKTOR USAHA KECIL MENENGAH - Santo Ajie Dhewanto (Faculty of Industrial Technology Universitas Islam Indonesia, 2018)
Bamboo is a new favourite material in the world of eco buildings in Indonesia. Design innovation of buildings will impact the high demand for bamboo that must be balanced with the rate of production in preserved bamboo supply. Existing problems in small and medium enterprises will be overcome by applying technopreneursip. Among them is by developing the tools that will help in improving the production. The application of technology must be balanced with education to small medium enterprises owner and the labor. Preservation by the boucherie-morisco method can increase production by the same amount of labor and time by 2.8 times than Vertical Soak Diffusion Method. Technologically supported enterprises will further strengthen the bargaining position in the bamboo supply business. The partnership pattern between academia and small and medium business sector will create synergy in developing technopreneurship in Indonesian grassroots.